The roles of forensic anthropology in fetal death investigation - Etty Indriati Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Physical anthropologist who has a training in forensic anthropology may be requested to give an expertestimony. In case of discovery of fetal remains, forensic scientist should understand on what main principles of medicolegal examination the evidences are based. In relation with fetal skeletal remains several investigations should be emphasized, i.e. the origin of the skeleton, the maturity compared with gestational age, the prematurity, whether the fetus is viable at birth, is the case an abortion one, the furnish data indicating the possible cause of death, and the time elapased between the interment and the discovery.The aim of this paper is to discuss the role of forensic anthropology in fetal death investigation and to present case studies of fetal death. The methods used in this study are those by various experts, to determine the age of fetuses. The material of the case study is an unknown fetal remain from Java-Indonesia sent by the law enforcement agency. The study was carried out in the Laboratory of Bioanthropology and Paleoanthropology Faculty of Medicine in July 1990. The result shows the Ohtsuki's method proved to be the most appropriate in this case, probably due to the similarity in body size between the Japanese and Indonesian. The result also shows that fetal age identification is extremely sensitive to measurement error. An error of 2 mm. Can lead to 3 months difference in fetal age, therefore, a caliper with 0.005 mm. accuracy is suggested. The conclusion drawn from this study is that physical anthropology is a necessary part of forensic investigation.Key Words: fetal remains investigation - Java origin - fetal age - identification method - forensic anthropology